1986
DOI: 10.2307/3430160
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium-Binding Proteins in the Mussel, Mytilus edulis

Abstract: Inducible cadmium-binding proteins (Cd-BP) in the mussel, Mytilu edulis, were resolved into two molecular weight components, designated Cd-BP,o and Cd-BP20, by gel-permeation chromatography on Sephadex G-75. Each of these two molecular weight components were further resolved into four subcomponents by DEAE-ion-exchange chromatography. All eight subcomponents bound cadmium and exhibited significant UV absorption at 254 nm and little absorption at 280 nm. Each subcomponent was purified and subjected to amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
4
7
0
Order By: Relevance
“…4). These values are similar to those of the half-cystine rich cadmium-binding proteins (8,11). A larger-scale purification of the unreduced HgBP20 fraction on DEAE-cellulose also resulted in the resolution of three major peaks corresponding to those above, but with considerably more overlap.…”
Section: Resultssupporting
confidence: 72%
“…4). These values are similar to those of the half-cystine rich cadmium-binding proteins (8,11). A larger-scale purification of the unreduced HgBP20 fraction on DEAE-cellulose also resulted in the resolution of three major peaks corresponding to those above, but with considerably more overlap.…”
Section: Resultssupporting
confidence: 72%
“…Box 12233, Research Triangle Park, NC 27709. tained a soluble cadmium-binding protein peak with an estimated molecular weight of 21,000 by Sephadex column chromatography. This value is about twice that reported for mammalian MT by this method (10) but similar to that reported from MT-like cadmium-binding proteins from mussels (2,6,12). The present study was undertaken to further characterize this protein peak in kidneys of the scallop Placopecten magellanicus and to determine whether it was a monomer or represented an aggregated form of lower molecular weight protein components.…”
Section: Introductionsupporting
confidence: 89%
“…Previous studies from a number of laboratories (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) have demonstrated the presence of cadmium-binding proteins (CdBP) in marine molluscs with properties that are both similar to and different from mammalian methallothionein (MT) (11,12). As previously noted (11), basic research on nonmammalian metal-binding proteins is of great potential value in elucidating not only the evolutionary pathway(s) of MT but also in gaining insight into its as yet unknown normal biological function.…”
Section: Introductionmentioning
confidence: 99%
“…The Sephadex G-75 column (5.0 x 50 cm) was eluted with 0.06 M or 0.01 M Tris-HCI buffer (pH 7.9 or 8.6), and fractions were monitored for Cd and for absorbance at 280 and 254 nm by using a Perkin-Elmer Model 305B atomic absorption spectrophotometer and ISCO Type 6 flow-through UV monitor, respectively. The peak Cd fractions corresponding to the CdBP described by Ridlington (9). Gels were stained either with Coomassie Blue or by the silver stain method using Bio-Rad silver stain kits.…”
Section: Isolation Of Oyster Cdbpmentioning
confidence: 99%